Near-threshold DD[bar] spectroscopy and observation of a new charmonium state - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2019)
Using proton-proton collision data, corresponding to an integrated luminosity of 9 fb−1, collected with the LHCb detector between 2011 and 2018, a new narrow charmonium state, the X(3842) resonance, is observed in the decay modes X3842→D0D¯0$$ X(3842)→ D^0{\overline{D}}^0 $$ and X(3842) → D+D−. The mass and the natural width of this state are measured to be